Finite Element Simulation to Predict Wrinkling in Low Carbon Steel Deep Drawing Process Using Isotropic Model - Wan Iryana, Wan Md Nor; Jasri, Mohamad (2015)
Deep drawing is one of important sheet metal processes used in manufacturing industry. It is a process for shaping sheet metals into cup-shaped products. Prediction of forming results can help to save material and production time. Hence, the finite element (FE) simulation provides the best answer to predict the early defects of forming product. This paper describes the use of ABAQUS/Standard FE simulation in a square cup deep drawing process using low carbon steel sheet metal. Here, the isotropic properties were used for the material’s input data in the FE model and then, the result was validate via experimental product. The objective of this paper is to study the effectiveness of FE model to predict the wrinkling defect in the deep drawing process. As the result, the FE model predicted the similar wrinkling pattern with the experimental product.